The effect of Empty Fruit Bunch (EFB) biochar and Ground Magnesium Limestone (GML) application on aluminium availability and rice growth performance grown in acid sulphate soil / Muhammad Lukman Alwi - Alwi, Muhammad Lukman (Faculty of Plantation and Agrotechnology, 2018)
Rice has a crucial role in food security but the production is limited grown in acid sulphate soil. Soil amendment using biological charcoal (biochar) from Empty Fruit Bunch (EFB) is one alternative as liming material in order to increase the soil pH. The utilization of acid sulphate soil for rice cultivation is one alternative option to increase the rice production. However, the main problem associated with this soil is due to its low pH and high content of exchangeable aluminium. The main objective this study was to investigate the effect of lime and biochar application on soil pH, aluminium availability and plant growth performance in acid sulphate soil. A pot experiment was conducted with the application different level of soil amendment: control (Non-amended soil), 4 tan/ha lime, combination of 2 tan/ha lime with 2.5 tan/ha biochar, 2 tan/ha lime with 5 tan/ha biochar and 2 tan/ha lime with 10 tan/ha biochar. From the finding, the application of lime can increase the soil pH from 3.72 to 4.08 and reduce the exchangeable aluminium concentration as compared to non-amended soil. In addition, the combination between lime and biochar also give good performance both plant heights and soil pH compare to (Non-amended soil). Therefore, it is recommended that the application of biochar together with lime also can be as good soil amendment and has potential in reducing aluminium availability on acid sulphate soil.